A form‐fitted three channel 31P, two channel 1H transceiver coil array for calf muscle studies at 7 T. Issue 6 (9th July 2014) - Goluch, Sigrun; Kuehne, Andre; Meyerspeer, Martin; Kriegl, Roberta; Schmid, Albrecht I.; Fiedler, Georg B.; Herrmann, Tim; Mallow, Johannes; Hong, Suk‐Min; Cho, Zang‐Hee; Bernarding, Johannes; Moser, Ewald; et al.
<x xml:space="preserve">Abstract</x> Purpose To enhance sensitivity and coverage for calf muscle studies, a novel, form‐fitted, three‐channel phosphorus‐31 (31P), two‐channel proton (1H) transceiver coil array for 7 T MR imaging and spectroscopy is presented. Methods Electromagnetic simulations employing individually generated voxel models were performed to design a coil array for studying nonpathological muscle metabolism. Static phase combinations of the coil elements' transmit fields were optimized based on homogeneity and efficiency for several voxel models. The best‐performing design was built and tested both on phantoms and in vivo. Results Simulations revealed that a shared conductor array for 31P provides more robust interelement decoupling and better homogeneity than an overlap array in this configuration. A static B1+ shim setting that suited various calf anatomies was identified and implemented. Simulations showed that the 31P array provides signal‐to‐noise ratio (SNR) benefits over a single loop and a birdcage coil of equal radius by factors of 3.2 and 2.6 in the gastrocnemius and by 2.5 and 2.0 in the soleus muscle. Conclusion The performance of the coil in terms of B1+ and achievable SNR allows for spatially localized dynamic 31P spectroscopy studies in the human calf. The associated higher specificity with respect to nonlocalized measurements permits distinguishing the functional responses of different muscles. Magn Reson Med 73:2376–2389, 2015. © 2014 Wiley Periodicals, Inc.